2022
DOI: 10.3389/fimmu.2021.800074
|View full text |Cite
|
Sign up to set email alerts
|

Collapsing Focal Segmental Glomerulosclerosis in Viral Infections

Abstract: Collapsing glomerulopathy represents a special variant of the proteinuric kidney disease focal segmental glomerulosclerosis (FSGS). Histologically, the collapsing form of FSGS (cFSGS) is characterized by segmental or global condensation and obliteration of glomerular capillaries, the appearance of hyperplastic and hypertrophic podocytes and severe tubulointerstitial damage. Clinically, cFSGS patients present with acute kidney injury, nephrotic-range proteinuria and are at a high risk of rapid progression to ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 80 publications
(93 reference statements)
1
19
0
2
Order By: Relevance
“…Afterwards, terminology has evolved in collapsing glomerulopathy to underline the rapid and catastrophic collapsing nature of the pathological process. CG is histologically defined by the formation of a pseudocrescent, i.e., a massive proliferation of cuboidal undifferentiated epithelial cell in the Bowman space, leading to a collapse of the capillary loops, regardless of the extracellular matrix accumulation eventually leading to focal and global glomerulosclerosis ( Muehlig et al, 2021 ) ( Figure 1 ). This pattern of injury represents a common endpoint from multiple etiologies (APOL1 risk variants, infections, drugs, ischemia, hematologic neoplasia and autoimmune disease), suggesting a common pathological mechanism rather than a specific cause ( Nicholas Cossey et al, 2017 ).…”
Section: Collapsing Glomerulopathymentioning
confidence: 99%
See 1 more Smart Citation
“…Afterwards, terminology has evolved in collapsing glomerulopathy to underline the rapid and catastrophic collapsing nature of the pathological process. CG is histologically defined by the formation of a pseudocrescent, i.e., a massive proliferation of cuboidal undifferentiated epithelial cell in the Bowman space, leading to a collapse of the capillary loops, regardless of the extracellular matrix accumulation eventually leading to focal and global glomerulosclerosis ( Muehlig et al, 2021 ) ( Figure 1 ). This pattern of injury represents a common endpoint from multiple etiologies (APOL1 risk variants, infections, drugs, ischemia, hematologic neoplasia and autoimmune disease), suggesting a common pathological mechanism rather than a specific cause ( Nicholas Cossey et al, 2017 ).…”
Section: Collapsing Glomerulopathymentioning
confidence: 99%
“…A typical clinical condition associated with collapsing pattern of injury at kidney biopsy is viral-mediated nephropathy, such as that observed with HIV, Parvovirus and SARS-CoV-2 infection ( Muehlig et al, 2021 ). Pseudocrescents, collapse of the capillary loops and podocyte multinucleation are predominant features of HIV-associated nephropathy ( Barisoni et al, 2000 ; Suzuki et al, 2009 ; Lasagni et al, 2013 ; Liapis et al, 2013 ; Al Hussain et al, 2017 ).…”
Section: Collapsing Glomerulopathymentioning
confidence: 99%
“…Further, we found that although not expressed under healthy baseline conditions, we show that the SARS‐CoV‐2 target ACE2 can be locally upregulated in damaged podocytes. As collapsing FSGS, a disease entity frequently associated with viral infections was also described in COVID‐19, 28 we apply the developed workflow to investigate the localization of SARS‐CoV‐2 RNA in a kidney biopsy of a patient suffering of a likely COVID‐19‐associated collapsing FSGS. Herein, we found that the main SARS‐CoV‐2 target were ACE2‐positive proximal tubule cells.…”
Section: Discussionmentioning
confidence: 99%
“…The barriers to establishing this method in other settings are low as only commercially available reagents are used, high-quality imaging systems are widely available, data analysis is performed in the open-source image analysis platform Fiji and the source code and pretrained DL networks are fully available.Further, we found that although not expressed under healthy baseline conditions, we show that the SARS-CoV-2 target ACE2 can be locally upregulated in damaged podocytes. As collapsing FSGS, a disease entity frequently associated with viral infections was also described in COVID-19,28 we apply the developed workflow to investigate the localization of SARS-CoV-2 RNA in a kidney biopsy of a patient suffering of a likely COVID-19-associated collapsing FSGS. Herein, we found that the main SARS-CoV-2 target were ACE2-positive proximal tubule cells.…”
mentioning
confidence: 99%
“…Viral infections, including human immunodeficiency virus (HIV), severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), cytomegalovirus (CMV), and parvovirus B19, are the most likely cause of glomerular podocyte damage and collapsing FSGS ( Muehlig et al, 2022 ). The main pathological features of HIV-associated nephropathy are the disappearance of the podocyte foot process, podocyte dedifferentiation, proliferation, apoptosis, podocyte detachment, and massive proteinuria ( Canaud et al, 2014 ).…”
Section: Factors Of Podocyte Injurymentioning
confidence: 99%